The potential roles of interactions between STAT3, Hsp90, and Hop in the maintenance of self-renewal in mouse embryonic stem cells - Setati, Mokgadi Michael (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2008)
Self-renewal of mouse embryonic stem (mES) cells is dependent upon the presence of leukemia inhibitory factor (LIF). LIF induces tyrosine phosphorylation and nuclear translocation of STAT3 (signal transducer and activator of transcription 3) which is thought to promote self-renewal by inducing key target genes. The molecular chaperone heat shock protein 90 (Hsp90) is involved in signal transduction pathways and regulates STAT3 activity in different cell types. However, the role of Hsp90 in regulating STAT3 activity in mES cells has not previously been investigated. The aim of this study was to investigate if Hsp90 interacts with STAT3 in mES cells and to determine if this interaction is important for the maintenance of self-renewal. It was found that when mES cells were cultured for 24.0 hours in the absence of LIF, the expression levels of total STAT3, tyrosine-phosphorylated STAT3 (pYSTAT3), and the pluripotency marker, Nanog, were down regulated. However, the expression level of Hsp90 was found to be slightly up-regulated over the same period. Significantly, it was found that the amount of STAT3 in differentiating mES cells available for binding to Hsp90 was decreased upon down-regulation of STAT3 by LIF withdrawal. Therefore, STAT3-Hsp90 interactions in mES cells were dependent on the presence of LIF, which suggested that the reduction in STAT3-Hsp90 interaction may have resulted from the low levels of STAT3. Despite a dramatic reduction in the expression levels of pYSTAT3 upon 24.0 hours of culture of mES cells in the presence of the STAT3 tyrosine phosphorylation inhibitor, cucurbitanin I, there was no obvious reduction in the levels of total STAT3, Oct-3/4 or Nanog. These results suggested that the levels of unphosphorylated STAT3 rather than pYSTAT3, maybe more important in the maintenance of mES cells self-renewal.
Keywords: Embryonic stem cells; Leukemia inhibitory factor; Cellular signal transduction; Heat shock proteins; Molecular chaperones